Safety of macitentan for the treatment of pulmonary hypertension: Real‐world experience from the OPsumit® USers Registry (OPUS) and OPsumit® Historical USers cohort (OrPHeUS). (14th November 2022) - McLaughlin, Vallerie V.; Channick, Richard; Kim, Nick H.; Frantz, Robert P.; McConnell, John W.; Melendres‐Groves, Lana; Miller, Chad; Ravichandran, Ashwin; Rodriguez‐Lopez, Josanna; Brand, Monika; Leroy, Sandrine; Wetherill, Graham; et al.
Abstract: Macitentan is an oral endothelin receptor antagonist for the management of pulmonary arterial hypertension (PAH). The OPsumit® USers Registry (OPUS) and the OPsumit® Historical USers cohort (OrPHeUS) medical chart review provide real‐world data for patients newly initiating macitentan. This study aims to describe the characteristics, safety profile, and clinical outcomes of PAH patients newly treated with macitentan in the combined OPUS/OrPHeUS data set. OPUS was a prospective, multicenter, long‐term, observational drug registry from April 2014 to June 2020. OrPHeUS was a retrospective, US, multicenter chart review: observation period October 2013 to March 2017. All analyses were descriptive. At registry closure in June 2020, the combined population consisted of 5654 patients, of whom 81.9% were diagnosed with PAH. For these 4626 patients, median duration of macitentan exposure observed was 14.5 (Q1 = 5.2, Q3 = 29.0) months; idiopathic PAH (54.8%) was the most common form of PAH; macitentan was initiated as monotherapy (37.9%), or as part of double (48.0%) or triple therapy (14.1%); discontinuation due to nonhepatic/hepatic adverse events occurred in 17.1%/0.3% of patients; 9.9% of patients experienced ≥1 hepatic adverse events; Kaplan–Meier estimates showed that at 1 year 59.9% (95% confidence interval: 58.3, 61.5) of patients were free from hospitalization and survival was 90.4% (89.3, 91.3). This analysis of real‐world data from the combined OPUS and OrPHeUS populations demonstrated that macitentan is well tolerated in a large, diverse population of PAH patients, with overall and hepatic safety profiles consistent with previous macitentan clinical trials.